The role of law in combating global warming - Ndung'u, Nugi James (My University, 2009)
This research report provides the reader with an overview of the current state of Earth as far as global warming and climate change is concerned. I describe how global warming is largely a consequence of humanoid behaviour from our past to our present behaviour focusing on self-centred materialism and consumerism. In the current economic paradigm, selfishness has become a prized commercial resource as humans continue to plunder, dominate and use earth’s resources with impunity. I explain ways in which the traditionally conceived views humans had concerning nature, including support by some religions, are changing, albeit slowly. This is accomplished by looking at changes in some concepts in two of the world’s major religions: Christianity and Islam. I describe the current physical state of the environment as the resource for human life. Because of its current state, I look at the importance of an ethical view of the environment. My major focus though is on the ways in which the emergence of the concept of international environmental law and its principles such as equitable utilization and apportionment have relevance and may prove to be the best deterrent in the attempt to stem global warming. I conclude this overview by making suggestions and recommendations concerning the Kyoto protocol - and how global warming can be tackled through an effective legal regimen.
Keywords: global warming; law; bioethics